2018
DOI: 10.5539/elt.v11n9p17
|View full text |Cite
|
Sign up to set email alerts
|

English in an EFL Context: Teachers’ and Learners’ Motivations for English Language Learning

Abstract: The present study explores the ways in which English is used in public discourse in Tehran-Iran and the motivations of Iranian -English as a Foreign Language (EFL) learners and teachers towards English language learning. The paper begins with an overview of different places in which English is used in Iran, such as media, public signs, traffic signs, advertisements, products, people's ordinary lives, and education. A cohort of 327 participants, including 168 Iranian EFL learners (male and female) and 159 exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…Rachana's story is consistent with some of the previous findings that have reported the expectations of learners including 'getting higher and better-qualified jobs' (Zarrabi, 2018) in the Iranian context, 'having a better job/earning more money' (Akçay et al, 2015) in the context of Turkey, and 'socio-economic and professional gains' (Kandel, 2018) or 'English for employability' (Poudel, 2016) in the Nepalese context.…”
Section: Job-and-career Opportunitiessupporting
confidence: 85%
See 1 more Smart Citation
“…Rachana's story is consistent with some of the previous findings that have reported the expectations of learners including 'getting higher and better-qualified jobs' (Zarrabi, 2018) in the Iranian context, 'having a better job/earning more money' (Akçay et al, 2015) in the context of Turkey, and 'socio-economic and professional gains' (Kandel, 2018) or 'English for employability' (Poudel, 2016) in the Nepalese context.…”
Section: Job-and-career Opportunitiessupporting
confidence: 85%
“…Eshghinejad's ( 2016) study involving 30 Iranian university freshmen of English as a foreign language (EFL) (19 males and 11 females) leads to the advocacy that "the nature of language learning… depends primarily on learners' motivation and attitude to learning a target language" (p. 3). The major reasons for learning EFL explored from Iranian teachers and students were: love for English (English sounds beautiful or luxurious to them), furthering education (passing IELTS/TOEFL/GRE, university entrance, pursuing higher education up to the doctoral degree, and accessing resources for knowledge), getting higher and better-qualified jobs, communication with the native speakers of English as well as a wider range of people from other nationalities and relatives living there, immigration (to migrate to the English speaking countries), entertainment (reading books and magazines in English for pleasure, watching English movies, listening to English songs, surfing the net in English and travelling to the English speaking countries), social credit (English as a matter of prestige), and need (no English means functionally illiterate) and parental influence (Zarrabi, 2018). Akçay et al (2015) conducted a study on children learning foreign languages at private institudes in Turkey explored seven reasons/expectations for their learning those languages (in the order of priority): talking to foreigners/tourists, entertainment (songs, games, movies, etc.…”
Section: Foreign Language Learners' Expectations: Wider Contextmentioning
confidence: 99%
“…Analysis of the questionnaires revealed that finding a job and learning English for academic purposes with having the first and the fourth rates respectively were two main reasons for the participants to learn English, highlighting the great importance of needs analysis for ESP courses (Rahman, 2015). Some previous research findings (Setiyadi et al, 2019;Tseng, 2014;Zarrabi, 2018) indicated that communication was the main reason for adult learners to learn English. However, the findings of this study based on the participants' responses to questionnaire items showed that the main reason for the participants in this new setting was related to building a professional career as well as finding a job, which highlighted the participants' instrumental motivation as well as the socio-economic factors urging them to improve their English knowledge.…”
Section: Discussionmentioning
confidence: 95%
“…Some EFL learners want to learn English to immigrate to English speaking countries more easily due to some socio-political factors. Zarrabi (2018) investigated the motivations of 168 Iranian EFL learners and 159 experienced Iranian EFL teachers who were once English language learners towards English language learning. A questionnaire with open-ended questions was administered for data collection The findings showed that 37% of EFL learners and 51% of EFL teachers chose to learn English because they loved it.…”
Section: Adult Efl Learners' Drivesmentioning
confidence: 99%
See 1 more Smart Citation